AB0486 Effect of Baseline Disease Duration on Development of Clinical Remission in the RA Patients Receiving Tocilizumab – Data from PMS with Tocilizumab in Biologics-Naïve RA Patients (First Bio) Study. (9th June 2015) - Mimori, T.; Atsumi, T.; Harigai, M.; Nishimoto, N.; Sumida, T.; Takeuchi, T.; Tanaka, Y.; Yamanaka, H.; Nakasone, A.; Takagi, N.; Ishiguro, N.
Abstract : Background: The all-patient registry PMS (PMS7901) of tocilizumab (TCZ) followed 7901 RA patients for 28 wk which showed that patients with a high probability of remission and a low probability of developing serious infection were most likely to be early and less advanced RA and had not received biologics previously. Objectives: The aim of this report is to investigate association of disease duration with effectiveness and safety in biologic-naïve RA patients treated with TCZ. Methods: FIRST Bio was a 52-wk observational postmarketing surveillance, which enrolled biologics-naïve RA patients who met the ACR/EULAR 2010 classification criteria for RA, experienced inadequate response or were intolerant to one or more synthetic DMARDs. Patients received intravenous TCZ (TCZ-IV; 8 mg/kg) every 4 wks with or without DMARDs. Patient characteristics and safety and effectiveness data were collected (last observation carry forward method). CDAI remission rate and incidence of adverse events (AEs) and serious AEs (SAEs) in each disease duration category (<2 years [n=240], 2 to <5 years [n=125], 5 to <10 years [n=118], ≥10 years [n=176]) were compared using the Mantel Haenszel chi square test. Results: Overall, 659 patients were analyzed. The mean disease duration was 7.5 years and was <2 years for 36.4% patients. At baseline CDAI values (Mean ± S.D.) was 23.7±12.7, 23.0±10.9, 21.2±9.5, and 24.5±12.2 in the disease duration categories <2 years, 2 to <5 years, 5 to <10 years, and ≥10 years, respectively. The mean CDAI improved from 23.3 at baseline to 6.6 at Wk 52 (p<0.0001). The CDAI remission rate (CDAI ≤2.8) at Wk 24 and 52 were 31.1% and 36.8%, respectively, in all patients; at Wk 24, this rate was 40.2%, 29.6%, 29.9%, 20.5% in the disease duration categories <2 years, 2 to <5 years, 5 to <10 years, and ≥10 years, respectively. However, at Wk 52, the CDAI remission rate in the ≥10 years group increased to 33.5%, although the corresponding rates in the other groups were stable between Wk 24 and 52. Consequently, no significant intergroup differences were observed in the remission rates at Wk 52. The incidence rate of AEs and SAEs was 36.7% and 12.3%, respectively. No significant intergroup differences were observed in the incidence of AEs and SAEs. Conclusions: This study suggests that long-term treatment with TCZ can improve the disease activity in established as well as newly diagnosed patients with RA. Disclosure of Interest: T. Mimori Grant/research support from: Asahi Kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Mitsubishi Tanabe, MDS, Nippon Kayaku, Nippon Shinyaku, Santen and Takeda, Speakers bureau: Astellas, Bristol-Myers Squibb, Chugai, Mitsubishi Tanabe and Taisho Toyama, T. Atsumi Grant/research support from: Chugai, Eisai, Bristol-Myers Squibb, Astellas, Daiichi Sankyo, Mitsubishi Tanabe, Speakers bureau: Astellas, Mitsubishi Tanabe, M. Harigai Grant/research support from: AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Mitsubishi Tanabe, Santen, Takeda and UCB, Consultant for: Bristol-Myers Squibb, Chugai and Janssen, Speakers bureau: AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe, Ono, Santen, Takeda, UCB and Pfizer, N. Nishimoto Grant/research support from: Chugai and Eisai, Consultant for: Chugai, T. Sumida Consultant for: Chugai, Speakers bureau: Chugai, T. Takeuchi Consultant for: AbbVie, Asahi Kasei, Asahi Kasei Medical, Astellas, Astra Zeneca, Bistol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, Janssen, Mitsubishi Tanabe, Novartis, Pfizer, Santen, SymBio, Takeda, Taishyo Toyama and Teijin, Speakers bureau: AbbVie, Asahi Kasei, Asahi Kasei Medical, Astellas, Astra Zeneca, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, Janssen, Mitsubishi Tanabe, Novartis, Pfizer, Santen, SymBio, Takeda, Taishyo Toyama and Teijin, Y. Tanaka Consultant for: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe and MSD, Speakers bureau: Abbvie, Actelion, Astellas, Astra Zeneca, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, GlaxoSmithKline, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Ono, Otsuka, Pfizer, Quintiles, Santen and UCB, H. Yamanaka Consultant for: AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Mitsubishi Tanabe, Nippon Kayaku, Pfizer, Takeda, Teijin and UCB, Speakers bureau: AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Mitsubishi Tanabe, Nippon Kayaku, Pfizer, Takeda, Teijin and UCB, A. Nakasone Employee of: Chugai, N. Takagi: None declared, N. Ishiguro Consultant for: AbbVie, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi Tanabe, Pfizer and Takeda, Speakers bureau: AbbVie, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi Tanabe, Pfizer and Takeda